2019
DOI: 10.4193/rhin19.172
|View full text |Cite
|
Sign up to set email alerts
|

Fipronil upregulates inflammatory cytokines and MUC5AC expression in human nasal epithelial cells

Abstract: Background: Airway inflammation and excessive mucin production are pathophysiological characteristics of airway diseases.Fipronil, a pesticide, is being extensively used in agriculture and veterinary medicine worldwide. However, this compound impairs immune function in non-target organisms. The present study aimed to evaluate the effect of fipronil on pro-inflammatory cytokine and mucus production and signalling pathways in human primary nasal epithelial cells. Methodology:The effect of fipronil on pro-inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
(25 reference statements)
1
2
0
Order By: Relevance
“…In the current study, FIP intoxication of Nile tilapia was associated with induction of cytokines expression that was decreased significantly in curcumin-supplemented fish. Similar mechanism of FIP toxicity was reported in human nasal epithelial cells, in which FIP was capable of increasing the expression of IL-1β, IL-8 and IL-6 through ERK1/2, p38 and NF-kB signalling pathways (Kwak et al, 2019). In Japanese quail, a significant overexpression in IL-6, TNF-α and NFk b in heart and lung tissues of birds after exposure to FIP toxicity which was reversed after recovery of exposure for 60 days (Khalil et al, 2019).…”
Section: Discussionsupporting
confidence: 74%
“…In the current study, FIP intoxication of Nile tilapia was associated with induction of cytokines expression that was decreased significantly in curcumin-supplemented fish. Similar mechanism of FIP toxicity was reported in human nasal epithelial cells, in which FIP was capable of increasing the expression of IL-1β, IL-8 and IL-6 through ERK1/2, p38 and NF-kB signalling pathways (Kwak et al, 2019). In Japanese quail, a significant overexpression in IL-6, TNF-α and NFk b in heart and lung tissues of birds after exposure to FIP toxicity which was reversed after recovery of exposure for 60 days (Khalil et al, 2019).…”
Section: Discussionsupporting
confidence: 74%
“…IF was employed to further verify the expression of MUC5AC in IL-13-stimulated JME/CF15 cells as previously described ( 26 ). Briefly, following fixation with 4% paraformaldehyde (Shanghai Aladdin Biochemical Technology Co., Ltd.) for 10 min at room temperature, the cells were incubated with 0.5% Triton X-100 (cat.…”
Section: Methodsmentioning
confidence: 99%
“…[2]. Mucins are the major components and contributors to the viscoelastic properties of mucus, and play an important role in maintaining the airway environment and function [3]. Prior studies have shown that regulation of mucin expression is an important strategy for the treatment of airway mucus hypersecretion in chronic inflammatory airway diseases [4].…”
Section: Introductionmentioning
confidence: 99%